La "desgraciada" conducta de la víctima: un problema de imputación - Vargas Pinto, Tatiana (Política criminal, 2014)
One of the problems of greatest practical impact, and underserved, is the influence of the victim prohibited behavior in the author responsibility determination. While the affected person seems to have no role in that, doubts begins when it also violates a rule. It is unclear the kind of conflict, how to solve it and what effects it has. From a practical and dogmatic basis the study seeks to answer such questions. Solutions are discussed with a specific proposal, from the normative point of view and attending real events (avoiding hypothetical considerations). From general regulated effects, the paper presents the main national jurisprudential trends and then makes a dogmatic analysis from a specific normative perspective. This test is presented with a known case by the fame of the accused that somehow appears as a guide.